Effect of molecular geometry and extended conjugation on the performance of hydrogen-bonded semiconductors in organic thin-film field-effect transistors. Issue 33 (8th June 2021) - Gómez, Paula; Cerdá, Jesús; Más-Montoya, Miriam; Georgakopoulos, Stamatis; da Silva, Iván; García, Antonio; Ortí, Enrique; Aragó, Juan; Curiel, David
Abstract : Hydrogen bonding has been used to direct the solid state packing of four polyheteroaromatic molecules. The correlation between structure and charge mobility has been evaluated in OFETs. Abstract : A general synthetic method has been used for the condensation of the 7-azaindole substructure at both extremes of centrosymmetric fused polyheteroaromatic systems. Four different aromatic spacers (benzene, naphthalene, anthracene and pyrene) that modify the molecular geometry and the π-conjugated surface have proved the ability of 7-azaindole to work as a building block that can control the crystal packing through reciprocal hydrogen bond interactions. Two possible self-assembled columnar arrangements have been observed as a result of the π–π interactions between hydrogen-bonded ribbon-like supramolecular structures. A detailed comparative analysis of the molecular organisation driven by hydrogen bonding and π-stacking, in combination with DFT calculations, has revealed an interesting evolution of the charge transport parameters. Organic thin-film field-effect transistors have been fabricated with the hydrogen-bonded semiconductors, reaching mobilities that demonstrate the potential of this supramolecular approach to control the molecular organisation and promote the electronic communication between the organic building blocks.